PENGEMBANGAN MEDIA INTERAKTIF VIDEO ANIMASI BERBASIS POWTOON MATERI BAGIAN TUBUH HEWAN BESERTA FUNGSINYA PADA PEMBELAJARAN IPA KELAS IV SD - Nabila Sayyida (Bajang Institute, 2023)
: This study aims to develop videoscribe animation learning media in science learning class IV. This study uses ADDIE's Research and Development (R&D) model, namely Analysis, Design, Development, Implementation, Evaluation. The instrument used is a questionnaire. Media product validation was carried out by two experts, namely: material experts and media experts. The validation results by media experts scored 97% in the very good category (SB). The results of validation by material experts scored 90% in the very good category (SB). From the results of the two expert validations, a score of 93% was included in the very good category (SB). Then in product trials carried out by three stages, namely: one to one, small group and field test. The results of the one to one stage trial got a score of 79% in the very good category (SB). The results of the small group trial got a score of 95% in the very good category (SB). The results of the field test stage got a score of 94% in the very good category (SB). From the three product trial results, a score of 89% was included in the very good category (SB) so that it was suitable for use as a medium in learning science about animal body parts and their functions in class IV SD. Keywords: Animas Learning Media; Powtoons; Animal Body Parts and Their Functions; Natural science